A Fluorescent Probe for Investigating the Activation of Anticancer Platinum(IV) Prodrugs Based on the Cisplatin Scaffold1. Issue 45 (17th September 2013) - Montagner, Diego; Yap, Siew Qi; Ang, Wee Han
<x xml:space="preserve">Abstract</x> Watching closely: A fluorescent probe was engineered to detect the clinically relevant platinum drug cisplatin within a complex cellular environment, thus providing a direct means for visualizing its cell entry and the activation of platinum(IV) prodrugs in cancer cells.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>